Characterising connectivity for fragmented landscapes in support of regional planning and impact assessment - Tiang, Darrel Chin Fung (2023)
Biodiversity loss resulting from habitat fragmentation and land use change is occurring at an increasing rate globally. Fragmentation can lead to genetic isolation within or between populations, due to loss in connectivity. The issue of ensuring ecological protection of fragmented areas must be addressed. Methods for accurately characterising connectivity within a landscape and integrating the study of connectivity loss into impact assessments is crucial. This thesis addresses this gap. It: (1) investigates the extent of ecological connectivity has been considered as part of infrastructure impact assessments (2) characterises connectivity for landscapes fragmented by agriculture, by considering how fine-scaled vegetation such as scattered trees support connectivity and the implications of ignoring such elements have on land use planning and (3) applies a spatially explicit scenario analysis of alternative road alignments and mitigation options to address common criticisms of the lack of consideration of connectivity in environmental impact assessments.